2003
DOI: 10.1046/j.1360-3736.2003.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Trust, collaboration, e‐learning and organisational transformation

Abstract: While theoretically distinct, learning and knowing are meshed in practice. This paper builds on this observation and argues that organisational transformation and the development of best practices in e-learning share some similar context. This is particularly evident when knowledge management perspectives are considered. Specifically, trust and collaboration are shown to be common enablers of both activities. A range of interrelated models is introduced with trust identified as prominent within a complex mix o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 12 publications
0
37
0
1
Order By: Relevance
“…In particular there is confusion as to whether the role is essentially technical, academic, administrative or a combination of all three (Conole et al, 2006). This lack of clarity in relation to what learning technologists actually do is unlikely to promote the kinds of 'trusting' relationships identified as being central to the success of collaborative teams (Mason and Lefrere, 2003). For example, Knowles and Kalata (2008) report on a case study where such a collaborative relationship was compromised due to academics being unsure about what they could legitimately ask learning technologists for help and assistance with.…”
Section: Collaboration and Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular there is confusion as to whether the role is essentially technical, academic, administrative or a combination of all three (Conole et al, 2006). This lack of clarity in relation to what learning technologists actually do is unlikely to promote the kinds of 'trusting' relationships identified as being central to the success of collaborative teams (Mason and Lefrere, 2003). For example, Knowles and Kalata (2008) report on a case study where such a collaborative relationship was compromised due to academics being unsure about what they could legitimately ask learning technologists for help and assistance with.…”
Section: Collaboration and Trustmentioning
confidence: 99%
“…However, it does little to respond to calls for more direction, clarity or help for stakeholders to "talk a common language" (McPherson and Nunes, 2007:241). Without this it is difficult to achieve the kind of consistency of purpose that Mason and Lefrere (2003) identify as being a core part of 'trust' in collaborative relationships. In their view consistency requires "semantic interoperability" and a need to establish "shared vocabularies " (2003:265).…”
Section: Direction Clarity and Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have suggested that KM activities are closely aligned with collaborative learning [35,36]. Davenport and Prusak [8] have identified four distinct knowledge conversion activities common in KM: Comparison (examining information against what is already known), Consequences (determining whether the information is sufficient to satisfy the knowledge need), Connections (identifying the relationship between this and other knowledge), and Conversation (exploring what others think).…”
Section: Knowledge Management Activitiesmentioning
confidence: 99%
“…CoPs are increasingly being used in the diffusion of knowledge by streamlining workflow and sustaining intellectual capital within and across organizational boundaries [8]. KS research emphasizes that a shared understanding and a common ground among people in a community are essential for collaboration and productive knowledge transfer [1].…”
Section: Ks and Trust In Copsmentioning
confidence: 99%